1986
DOI: 10.1182/blood.v68.4.886.886
|View full text |Cite
|
Sign up to set email alerts
|

Trial of repeated low-dose aspirin in diabetic angiopathy

Abstract: We compared the ability of aspirin to suppress platelet aggregation and thromboxane synthesis in ten normal subjects and ten patients with diabetic angiopathy and high rate of entry of new platelets into the circulation. When single doses of 100 to 1,000 mg aspirin were ingested daily for 1 month, there were time gaps between doses in which platelets from diabetics and normals aggregated and formed thromboxane ex vivo in response to the combination of arachidonic acid plus collagen. Similar gaps were also foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 34 publications
0
34
0
2
Order By: Relevance
“…A distinction has been made between studies comparing the same or a different overall daily dose. For comparisons of the same overall dose, most results across five studies 36,37,39,40,42 did not show statistically significant differences in platelet function; two studies 15,39 found a significant difference (favoring twice-daily dosing) with one but not the other of two PFTs used, respectively. There is thus little evidence to suggest a potential benefit from twice-daily dosing in these populations (Type 2 diabetes mellitus (T2DM) with or without CAD/CVD, or ischemic heart/cerebrovascular disease (IHD/ ICD)).…”
Section: Effect On Platelet Functionmentioning
confidence: 93%
See 1 more Smart Citation
“…A distinction has been made between studies comparing the same or a different overall daily dose. For comparisons of the same overall dose, most results across five studies 36,37,39,40,42 did not show statistically significant differences in platelet function; two studies 15,39 found a significant difference (favoring twice-daily dosing) with one but not the other of two PFTs used, respectively. There is thus little evidence to suggest a potential benefit from twice-daily dosing in these populations (Type 2 diabetes mellitus (T2DM) with or without CAD/CVD, or ischemic heart/cerebrovascular disease (IHD/ ICD)).…”
Section: Effect On Platelet Functionmentioning
confidence: 93%
“…32 Once-vs. twice-daily (or more) administration. The 11 studies 15,[35][36][37][38][39][40][41][42][43]45 (see Table 1) comparing a different frequency of daily dosing were heterogeneous in terms of study design, duration of treatment, and population (diabetes, CAD, CVD, ET); all were short-term studies with up to 2 months per treatment period reporting as their main outcome PFT results, mainly light transmission aggregometry (LTA), serum thromboxane levels, and VerifyNow Aspirin. Where possible, these results have been presented in forest plots (see Figures 3, 4), with the remaining results tabulated (see Supplementary File Tables 3-7).…”
Section: Effect On Platelet Functionmentioning
confidence: 99%
“…20,35 Other major thrombolytic studies, and other investigations of aspirin use in at risk patients with diabetes, show similar benefit to that in non-diabetic subjects (Figure 2), 36,37 even though some reports suggest that diabetic patients need a higher dose of aspirin than do patients without diabetes. 38 It would appear logical to initiate aspirin treatment with thrombolytic therapy in diabetic patients, and continue in a dose of 300 mg daily of enteric coated aspirin long term. 37…”
Section: Aspirinmentioning
confidence: 99%
“…Second, platelet turnover may be accelerated in diabetic patients. 25 Thus, new platelets without cyclooxygenase blockade may enter the circulation as blood aspirin levels fall, if short-acting preparations are used. Furthermore, a very low blood level of aspirin is all that is needed to block cyclooxygenase and, hopefully, to encourage endothelial release of prostacyclin.…”
Section: Table 2 Secondary Prevention Trials-antiplatelet Agentsmentioning
confidence: 99%